Few glitters are original gold: Strengthening brand citizenship through identification, knowledge, and ownership in a mediating role of brand pride. Issue 3 (18th July 2019) - Ansari, Aisha Rehman; Kashif, Muhammad
Abstract : Purpose: The purpose of this paper is to investigate the role of brand identification (BI), brand knowledge (BK) and brand psychological ownership (BPO) to predict brand citizenship behaviours (BCB) in a mediating role of brand pride. Design/methodology/approach: Using survey data collected from 372 front line employees (FLEs), employed in different banks in Pakistan, the path analysis through structural equation modelling procedures is used to perform data analysis. Findings: The results show that BI, BK and BPO strongly predict BCB in a mediating role of brand pride. Practical implications: The results have pragmatic value to guide managers and marketing policymakers to develop a brand culture where the company as a brand is internally owned by its employees. The supervisors should offer FLEs with opportunities to speak up and must socialize with them so that communication touch points can be established and strengthened. Furthermore, delegation of authority and positive enforcement are important tools to trigger psychological ownership among FLEs. Originality/value: Three antecedents (i.e. BI, BK and BPO) to advocate and channelize brand-oriented citizenship behaviours are unique to this study. Furthermore, the mediating role of brand pride is yet another unique contribution.